Industrial training report: Bersatu Lagenda Management - Mohamed Azhar, Muhammad Afiq (Universiti Teknologi MARA, Perlis, 2024)
As part of my Bachelor's degree requirements, I had the chance to work as an intern at Bersatu Lagenda Management, a well-known Malaysian company that helps Bumiputera buy and sell homes all over the country. I had many jobs to do during my internship. I helped keep clients and other important people updated by talking to them and making sure they knew what was going on. I also worked on projects linked to sustainability and made sure that the company's digital files were well organised. A big part of my internship was looking at the company's chances, threats, strengths, and weaknesses. This meant looking at a lot of different things, such as politics, the economy, social problems, technology, the environment, and the law. The good things I found are that Bersatu Lagenda Management knows how to help Bumiputera buy and sell homes. Weaknesses: They spend a lot of money and depend too much on certain ways. Opportunities: Going into new areas could be profitable, and the economy is getting better. Threats: The housing market isn't always stable, and rivals are putting pressure on you. I gave Bersatu Lagenda Management some ideas to help them. They should keep making their services better and make choices based on more data. Plus, they need to find ways to work smarter and get to more people. They could grow if they moved into new areas and made their processes better. They also need to be ready to change with the times and what people want from them. It might be hard for Bersatu Lagenda Management to keep up with the changes in the home market if they don't listen to these ideas.